Suicide and Suicide-Related Behaviors: A Multi-Perspective Explanation and Implications for Suicide Prevention Strategy in Vietnam - Dinh, Phuong Linh (H. : ĐHQGHN, 2019)
Suicide and suicide-related behaviors have been widely recognized as a serious public health issue and have become a popular topic among the scholar community. Thus, in Vietnam, the exact statistics of suicide have not yet been unveiled and there lacks a comprehensive system to record cause-of-death in the country. This article discusses the controversy around terminology in suicidology and seeks to explain the act of suicide under a multi-disciplinary prism. International experiences on suicide prevention are also analyzed, which helps to propose some implications for the suicide prevention strategy in the country.